Potensi penerimaan retribusi pelayanan pasar dan kontribusi serta prospeknya terhadap pendapatan asli daerah kota samarinda - Dharma Hammam Nur Mubarok (FORUM EKONOMI, 2016)
The aim of this study is to find out the potency of market services retribution and its contribution and prospects as the source of district own source revenue in Samarinda. The source of this data is secondary data. The secondary data of this study are consisted of the realization report of  district  own  source revenue in Samarinda,  the  report  of  the  market  service  potency  in Samarinda and the realization report of market services retribution in  Samarinda by using descriptive statistic method. The used method of this study are analysis of market potential, analysis of the level of contribution and trend analysis. The result of this study shows that in first analysis, the calculation of market services potential retribution in Samarinda within a year indicates a great potential, but the realization of market service retribution in last five years still had not exceeded the total of existing potential, in the second analysis, the contribution of market services retributions as  as the source of district own source revenue in Samarinda is placed on “very poor” indicator means that there was decreasing contributions in every years, and  in the third analysis,  the prospect  of market  services retribution in  Samarinda  shows positive result (increasing) for five years later.Keywords: Retributions, Own Source Revenue, Market Services